Contrasting Anticancer Activity of Half-Sandwich Iridium(III) Complexes Bearing Functionally Diverse 2‑Phenylpyridine Ligands - Millett, Adam J; Habtemariam, Abraha; Romero-Canelón, Isolda; Clarkson, Guy J; Sadler, Peter J (Organometallics, 2015)
We report the synthesis, characterization, and antiproliferative activity of 15 iridium(III) half-sandwich complexes of the type [(η5-Cp*)Ir(2-(R′-phenyl)-R-pyridine)Cl] bearing either an electron-donating (−OH, −CH2OH, −CH3) or electron-withdrawing (−F, −CHO, −NO2) group at various positions on the 2-phenylpyridine (2-PhPy) chelating ligand giving rise to six sets of structural isomers. The X-ray crystal structures of [(η5-Cp*)Ir(2-(2′-fluorophenyl)pyridine)Cl] (1) and [(η5-Cp*)Ir(2-(4′-fluorophenyl)pyridine)Cl] (2) exhibit the expected “piano-stool” configuration. DFT calculations showed that substituents caused only localized effects on the electrostatic potential surface of the chelating 2-PhPy ligand of the complexes. Hydrolysis of all complexes is rapid, but readily reversed by addition of NaCl. The complexes show preferential binding to 9-ethylguanine over 9-methyladenine and are active catalysts for the oxidation of NADH to NAD+. Antiproliferative activity experiments in A2780 ovarian, MCF-7 breast, A549 lung, and HCT116 colon cancer cell lines showed IC50 values ranging from 1 to 89 μM, with the most potent complex, [(η5-Cp*)Ir(2-(2′-methylphenyl)pyridine)Cl] (13) (A2780 IC50 = 1.18 μM), being 10× more active than the parent, [(η5-Cp*)Ir(2-phenylpyridine)Cl], and 2× more active than [(η5-CpxPh)Ir(2-phenylpyridine)Cl]. Intriguingly, contrasting biological activities are observed between structural isomers despite exhibiting similar chemical reactivity. For pairs of structural isomers both the nature and position of the functional group can affect the hydrophobicity of the complex. An increase in hydrophobicity resulted in enhanced cellular-iridium accumulation in A2780 ovarian cells, which generally gave rise to an increase in potency. The structural isomers [(η5-Cp*)Ir(2-(4′-fluorophenyl)pyridine)Cl] (2) and [(η5-Cp*)Ir(2-phenyl-5-fluoropyridine)Cl] (4) preferentially localized in the cytosol > membrane and particulate > nucleus > cytoskeleton. This work highlights the strong dependence of biological behavior on the nature and position of the substituent on the chelating ligand and shows how this class of organometallic anticancer complexes can be fine-tuned to increase their potency without using extended cyclopentadienyl systems.